Pelatihan Metode Tajwid Dr. Ayman dengan Pendekatan Komunikasi Interpersonal dalam Meningkatan Kualitas Pembelajaran Al-Quran - Nurwahida, Nurwahida; Matsam, Risnawati; Abdurrahman, Abdurrahman; Muzakkir, Muzakkir (Universitas Teuku Umar, 2025)
Teaching the Quran, especially in the field of tajweed, requires more competence than just mastery of teaching materials, educators' communication skills also determine the effectiveness of learning. This article discusses Dr. Ayman's tajweed method training applied to 26 educators teaching religious subjects, with a participatory approach and integration of interpersonal communication. The training aims to improve technical skills in reading the Quran and equip educators with the skills to deliver material empathetically, clearly, and interactively. Training methods included strengthening tajweed theory, hands-on practice, teaching simulations, and developing communication skills. The results of the training show that an approach that combines mastery of the material with interpersonal skills can create a collaborative learning atmosphere, increase motivation, and improve the effectiveness of teaching tajweed in the classroom. Periodic post-training evaluations also ensure the continuity of improving educators' competence in teaching the Quran according to the correct rules and touching the spiritual aspects of students.